At the Intersection of Method and Empowerment: Reflections from a Pilot Photovoice Study with Survivors of Human Trafficking. Issue 4 (2nd October 2022) - Lockyer, Sue; Koenig, Christopher J.
ABSTRACT: As human trafficking research increases, attention to ethical research methods with trafficking survivors is important to ensure equitable processes and reliable results for policy and social services. This article first describes Photovoice, a participatory research method that asks individuals to take photos and then to narrate the significance of those photos to develop critical consciousness, and second reflects on the Photovoice method for use with survivors of human trafficking. We outline a pilot Photovoice research project with survivors of human trafficking ( n  = 4) to consider the strengths, challenges, and opportunities that Photovoice offers for basic and applied research. When implemented as part of a trauma-informed and resilience-oriented framework, Photovoice promotes participants' sense of empowerment, self-competence, and self-esteem. We discuss how Photovoice can support vulnerable populations, including survivors of human trafficking, while also generating rich and nuanced research data. Our reflections on the lessons learned conducting Photovoice research will support others to implement the method to empower individuals who have survived human trafficking and will promote research contributing to a more just, peaceful, and inclusive society.